A Benzo[1, 2‐b:4, 5‐b′]Difuran Based Donor Polymer Achieving High‐Performance (>17%) Single‐Junction Organic Solar Cells with a Fill Factor of 80.4%. Issue 33 (19th July 2022) - Yi, Jicheng; Pan, Mingao; Chen, Lu; Chen, Yuzhong; Angunawela, Indunil Chathurangani; Luo, Siwei; Zhang, Ting; Zeng, Anping; Chen, Jian; Qi, Zhenyu; Yu, Han; Liu, Wei; et al.
Abstract: In the field of non‐fullerene organic solar cells (OSCs), most of the promising polymer donors are based on benzo[1, 2‐b:4, 5‐b′]dithiophene (BDT) units while benzo[1, 2‐b:4, 5‐b′]difuran (BDF)‐based polymers have drawn less attention since the efficiencies of BDF polymer‐based devices are generally lower than those of BDT polymer‐based ones. In this contribution, the BDT unit in a polymer donor named D18 is replaced with a BDF unit, and a new polymer named D18‐Fu is synthesized. As a highly‐crystalline molecule named Y6‐1O is chosen as the acceptor, the efficiency of binary devices based on D18‐Fu can reach 16.38%. Furthermore, when one of fullerene derivatives PC71 BM is added, the ternary devices based on D18‐Fu achieve an efficiency of 17.07% and a high fill factor (FF) of 80.4%, both of which are the highest values among those of BDF polymer‐based devices. For comparison, D18‐based ternary devices show an inferior efficiency of 15.61% mainly due to the lower FF of 73.9%. Subsequent characterization reveals that D18‐Fu possesses a more coplanar molecular geometry, leading to better morphology and higher charge mobility for a promising FF. The high performance shown in this work demonstrates the potential role of BDF units in the design of polymer donors for highly efficient OSCs. Abstract : The authors design and synthesize a new benzo[1, 2‐b:4, 5‐b′]difuran (BDF)‐based polymer donor named D18‐Fu. The D18‐Fu‐based devices can achieve an excellent efficiency of 17.07% with a high fill factor (FF) of 80.4%, both of which are the highest values among those of BDF polymer‐based devices.